Hydrodynamic performance assessment of emerged and sub-merged semicircular breakwaters under random waves: An experimental and empirical study - Faris Ali Hamood Al-Towayti; Hee Min Teh; Zhe Ma; Idris Ahmed Jae; Agusril Syamsir (PLoS ONE, 2025)
Mangrove ecosystems and other coastal protection structures are essential barriers protecting coastal populations from the damaging effects of wave energy and increasing sea levels. This study uses a semicircular breakwater (SBW) model in an effort to develop coastal protection measures. The hydrodynamic characteristics of the SBW under random wave conditions, including the transmission coefficient, reflection coefficient, and energy loss coefficient, were thoroughly investigated using physical model experimentation. The main objectives encompass understanding the behavior of the SBW model, developing empirical equations to estimate hydraulic characteristics, and enhancing coastal protection structures to facilitate the preservation and expansion of mangrove ecosystems. Hydrodynamic features of the SBW model were assessed across a spectrum of wave conditions. Experimental testing in a wave flume encompassed a range of relative water depths (d/h), including d/h = 0.667 for an emerged SBW, d/h = 1.000 for an alternatively submerged SBW, and fully submerged conditions for d/h = 1.333 and 1.667. Wave steepness (Hi/L) varied from 0.02 to 0.06, and wave periods ranged from 0.8 to 2.5 seconds. Notably, analysis of an emerged SBW with d/h = 0.667 revealed superior wave attenuation compared to d/h = 1.000, 1.333, and 1.667 configurations.